Intra-articular methotrexate. Clinical and laboratory study in rheumatoid and psoriatic arthritis. Issue 4 (August 1978) - Hall, G H; Jones, B J; Head, A C; Jones, V E
Abstract : The effects of intra-articular methotrexate (MTX) were compared with saline in 20 patients with persistent knee effusions due to rheumatoid arthritis (15) and psoriasis (5) in a double-blind pilot study. Clinical improvement was seen in most patients given either MTX or saline and was attributed to joint irrigation during arthroscopy and the placebo effects. MTX had a local anti-inflammatory effect in the psoriatic arthropathies; the percentages of polymorphonuclear cells and pyroninophilic mononuclear cells in synovial fluids fell sharply. Intraarticular hydrocortisone acetate was not anti-inflammatory in 2 psoriatic patients treated subsequently. The anti-inflammatory action of MTX in joints may resemble its effectiveness in controlling the rash of psoriasis.